2013
DOI: 10.3390/molecules181011978
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antibacterial Evaluation of Some Novel Imidazole and Benzimidazole Sulfonamides

Abstract: Several new substituted sulfonamide compounds were synthesized and their structures were confirmed by 1 H-NMR, 13 C-NMR, FT-IR, and mass spectroscopy. The antibacterial activities of the synthesized compounds were screened against standard strains of six Gram positive and four Gram negative bacteria using the microbroth dilution assay. Most of the compounds studied showed promising activities against both types of bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 41 publications
(45 reference statements)
1
46
0
1
Order By: Relevance
“…The minimum inhibitory concentration for complex 5 is small suggesting its high biological efficacy. The reason can be explained based on the Overtone's concept [42] and Tweedy's Chelation theory [43]. The polarity of the metal ion decreases after the chelation owing to the overlap of the planar ligand orbitals which causes increase in the delocalization of p-electrons over the whole chelate ring.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The minimum inhibitory concentration for complex 5 is small suggesting its high biological efficacy. The reason can be explained based on the Overtone's concept [42] and Tweedy's Chelation theory [43]. The polarity of the metal ion decreases after the chelation owing to the overlap of the planar ligand orbitals which causes increase in the delocalization of p-electrons over the whole chelate ring.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…18,19 From the ILs' structure point of view, Poly-functionalized heterocyclic compounds containing imidazole and its derivatives are acquiring more importance due to their biological activity. 46 However, many research works dealt with geminal di-cationic ILs synthesis when it comes to their design, 6,7,9,18,[47][48][49][50][51][52] while limited studies have considered dicationic ILs with high rigid spacer. imidazolium, benzimidazolium, pyridinium, pyrrolium, pyrrolidinium and ILs with bridged structures.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that sulfonamide compounds were used as antibacterial [7][8][9], antifungal [9,10], antiviral [11], anticancer [12], antinflammatory, analgesic [13][14][15], and antibacterial agents [16]. Also, a wide variety of benzimidazole derivatives have been described for their chemotherapeutic importance [17][18][19][20][21][22][23] and oxazole derivatives play very important role in the manufacturing process of various biologically active drugs as anticancer, antimicrobial, antidiabetic and antiobesity [24,25].…”
Section: Introductionmentioning
confidence: 99%